Security and loss prevention an introduction - Purpura, Philip P., 1950- (Elsevier, 2013)
Examines security in a range of contexts, spanning corporate issues such as personnel management and business continuity, and encompassing topics of terrorism and border security. This book covers changes in laws, various strategies of asset protection, and the technology of security and loss prevention.